HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI DENGAN PERILAKU SEKS PRANIKAH REMAJA PENGHUNI KOS-KOSAN DI KELURAHAN LIMBA U 1 KECAMATAN KOTA SELATAN KOTA GORONTALO - Adam, Wirdawaty (Sainstek, 2011)
Relations With Reproductive Health Knowledge Sex Behavior Adolescent premarital Kos-Kosan Inhabitants in District 1 District Limba U Gorontalo City South City. Teenage is a period of transition from child to adult stage of which the period varies social and cultural factors. One of the factors that influence adolescent premarital sexual behavior is the lack of knowledge about reproductive health. This study aims to determine the relationship of reproductive health knowledge with premarital sexual behavior of adolescent residents in the village kos-kosan Limba U 1 South City district of Gorontalo city. Bersidat research is descriptive analysis. Sampling Simple Random Sampling in to 110 respondents, ie 17-24 years old and unmarried. Obtained using data collection techniques kursioner. Processing data using SPSS 17 for Chi-square test. The results overall showed that 43 respondents (39.09%) have less knowledge, 40 respondents (36.36%) had good knowledge. Based on premarital sexual behavior obtained by 65 respondents (59.09%) had less behavior and 21 respondents (19.09%) had good behavior. From the calculation results obtained by Chi-square p-value = 0.002 (p-value